2002
DOI: 10.1063/1.1449943
|View full text |Cite
|
Sign up to set email alerts
|

Bimetallic Ag–Au nanoparticles: Extracting meaningful optical constants from the surface-plasmon extinction spectrum

Abstract: We report an approach for extracting the optical constants of bimetallic Ag–Au nanoparticles from the measured surface-plasmon (SP) extinction spectra. The dielectric function of the metal is expressed as an analytic function of the wavelength in which the interband (and all other non-Drude) contributions to the dielectric function are represented by a sum of Lorentz functions. This expression is then used to fit the experimental extinction spectra to appropriate functions based on Mie theory. Three Lorentz fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

20
199
1
7

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(227 citation statements)
references
References 28 publications
20
199
1
7
Order By: Relevance
“…The plasmon bands are slowly red-shifted from Nano Res (2009) 2: 607 616 at room temperatures. The nanoparticle alloying can, in principle, result from an increase in the diffusion coefficient of the metals, because the melting point lowers as their size decreases [30]. The melting points of bulk Au and Ag are 1064.18 ºC and 961.78 ºC, respectively [22].…”
Section: Resultsmentioning
confidence: 99%
“…The plasmon bands are slowly red-shifted from Nano Res (2009) 2: 607 616 at room temperatures. The nanoparticle alloying can, in principle, result from an increase in the diffusion coefficient of the metals, because the melting point lowers as their size decreases [30]. The melting points of bulk Au and Ag are 1064.18 ºC and 961.78 ºC, respectively [22].…”
Section: Resultsmentioning
confidence: 99%
“…In order to fit the ellipsometric data, two peaks are required to model the SPR for the as-deposited samples while only one peak is necessary for the annealed samples. This double-peak structure of the SPR for the as-deposited samples has been previously associated to a core-shell structure (one peak associated to the core material and the other to the shell material) 4,5 . Upon annealing, alloying of the particles takes place, leading to a single-peak SPR 6,7 .…”
Section: Resultsmentioning
confidence: 99%
“…This is a clear indication that Au core Ag shell nanoparticles are constituted by variable composition objects, with a continuous inclusion in the core of silver atoms coming from the shell. Several authors [15,16,17] reported the fact that the colloidal dispersion of metallic particles composed by an Au-Ag solid solution is obtained at long irradiation times, is proven by the existence of this single plasmon resonance, ruling out the possible formation of core-shell structure. Au-Ag NPs.Morphology and crystal structure of Au NPs, Ag NPs and Au-Ag composite NPs was examined using X-Ray diffraction spectrophotometer (XRD, SHIMADZU, 6000).…”
Section: Results and General Discussionmentioning
confidence: 99%